Investigating The Surface Characteristics of Dip Coated 3D Printed ABS Specimens - Satyanarayana, Poornaganti; Narayan, Yeole Shivraj; Prakash, Kode Jaya; Cherukuri, Jyotsna; D., Maneiah (International Journal of Integrated Engineering, 2023)
In the past few years, FDM basedpolymer 3D printing process has flourished mainly with ABS filaments as a thermoplastic source. Food packing, medical, marine and agriculture industries employdevices and other usable items made of polymers. Utilizing layered fabrication components in these areascompelthem to have self-cleansing, anti-freezing and corrosion resistant surfaces. It is generally complex and expensive to prepare hydrophobic coatings.The present work is related to the development of a surface coating on 3D printed ABS specimens with the mentioned properties. 3D printed specimens were fabricated using Flash Forge 3D printer without any modifications, and the hydrophobic coatings were achieved by dip coating process using Tricalcium phosphate-chitin solutions with a ratio of 70:30. Static contact angle measurement was employedin gaging wettability impact on dip coated 3D printed specimens. By using digital vernier calipers and profilometer (SJ410), dimensional accuracy and surface roughness were assessed pre and post-coating. According to ASTM D570-98, water absorption tests were conducted at different time intervals. Results of the experiment showed that the hydrophobic solutions had been successfully synthesized. The maximum contact angle was achieved for solution 1(4g of tricalcium phosphate solution with 0.3g chitin solution) i.e., 109.3°. Improvement in the textureof 3D printed ABS surfaceswas observed after dip coating. Dip-coated 3D printed ABS specimens exhibited minimal absorption based on their weight gain per area.